2012
DOI: 10.1016/j.bbalip.2011.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton disruption in J774 macrophages: Consequences for lipid droplet formation and cholesterol flux

Abstract: Macrophages store excess unesterified cholesterol (free, FC) in the form of cholesteryl ester (CE) in cytoplasmic lipid droplets. The hydrolysis of droplet-CE in peripheral foam cells is critical to HDL-promoted reverse cholesterol transport because it represents the first step in cellular cholesterol clearance, as only FC is effluxed from cells to HDL. Cytoplasmic lipid droplets move within the cell utilizing the cytoskeletal network, but, little is known about the influence of the cytoskeleton on lipid dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…This revealed several actin-binding proteins (Supplementary Table 1), including NMIIa (encoded by the MYH9 gene), a structural component of contractile actin filaments. NMIIa has earlier been identified in the LD proteome of several organisms101112, but its functional role at LDs remains unknown.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This revealed several actin-binding proteins (Supplementary Table 1), including NMIIa (encoded by the MYH9 gene), a structural component of contractile actin filaments. NMIIa has earlier been identified in the LD proteome of several organisms101112, but its functional role at LDs remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Actin and actin-binding proteins have been reported to be associated with LDs101112. In murine macrophages, pharmacological disruption of the actin cytoskeleton reduces LD size and lipid storage10 and in 3T3-L1 cells, inhibition of actin dynamics through cofilin-1 depletion disrupts adipogenesis and lipid storage13.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 58 ]. In addition, several studies suggest that cell junction-related pathways are also involved in lipid deposition [ 52 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, DEGs were also significantly enriched ( p < 0.05) in calcium signaling pathway and junction-related pathways (focal adhesions, cell adhesion, gap junction, tight junction, regulation of actin cytoskeleton and ECM-receptor interaction). Many studies have shown that the cell junction-related pathways may contribute to lipid deposition [9, 53, 54]. These results indicated that the above pathways might be the key pathways for lipid deposition in chicken pectoralis muscle tissue and a possible molecular regulatory network was constructed (Fig.…”
Section: Discussionmentioning
confidence: 89%